ALIH KODE DAN CAMPUR KODE DALAM FILM JUST MOM KARYA JEIHAN ANGGA - Ashari, Hartina Prapti; Patriantoro, Patriantoro; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Studying code-switching and code-mixing is intriguing as mastering multiple languages is essential and enhances the charm of movies. This study focuses on recognizing the patterns and reasons for codeswitching and code-mixing in the movie Just Mom by Jeihan Angga and how it can be utilized in teaching Indonesian language to twelfth graders. This research utilizes a descriptive methodology along with a qualitative approach. The film Just Mom is the source of data for this study, which consists of the dialogues featuring both code-switching and code-mixing in the film Just Mom. Observation and taking notes are the data analysis methods being utilized. This study yielded 36 pieces of speech data, including 9 cases of code-switching and 55 cases of code-mixing. Code-switching is influenced by three main factors: speaker or interlocutor factors with 3 data points, interlocutor factors with 2 data points, and situational and topical factors with 4 data points. Factors that affect code-mixing are categorized into two groups: speaker factors and data, and linguistic factors which are then subdivided into three parts: speaker and personal factors and data, interlocutor factors and data, and prestige factors and data.